Rural youth and struggle for citizenship: limits and possibilities of socialization - Olivera Rodríguez, Inés (2009)
This article is based on ethnographic fieldwork I conducted between January and March of 2007 in a small rural village on the north coast of Peru as part of the research for my Master’s Degree thesis. It addresses the ways that the rural youth give their own school experience. During the fieldwork, I lived in Chaquira for two months and conducted 18 in depth interviews with young people. I also visited the local high school and had informal conversations with different demographic groups in the village, mainly young parents (between 30 and 45 years old). Based on a definition of citizenship and a description of the youth’s every day life, this paper analyzes the processes of exclusion, not only as a structural problem, but also as the situation of internal oppression within a determined social space. The objective is to think about social space of rural youth as spaces that enable or hinder the formation of participatory citizens. For this reason, I focuse on the aspects of school experiences and on socia1 factors that contribute to the construction and exercise of citizenship.